Neurodegenerative diseases: exercising towards neurogenesis and neuroregeneration - Ang, Eng-Tat; Tai, Alex; Lo, Shun-Qiang; Seet, Raymond; Soong, Tuck Wah (Frontiers in Aging Neuroscience, 2010)
Currently, there is still no effective therapy for neurodegenerative diseases (NDD) such as Alzheimer’s disease (AD) and Parkinson’s disease (PD) despite intensive research and on-going clinical trials. Collectively, these diseases account for the bulk of health care burden associated with age-related neurodegenerative disorders. There is therefore an urgent need to further research into the molecular pathogenesis, histological differentiation, and clinical management of NDD. Importantly, there is also an urgency to understand the similarities and differences between these two diseases so as to identify the common or different upstream and downstream signaling pathways. In this review, the role iron play in NDD will be highlighted, as iron is key to a common underlying pathway in the production of oxidative stress. There is increasing evidence to suggest that oxidative stress predisposed cells to undergo damage to DNA, protein and lipid, and as such a common factor involved in the pathogenesis of AD and PD. The challenge then is to minimize elevated and uncontrolled oxidative stress levels while not affecting basal iron metabolism, as iron plays vital roles in sustaining cellular function. However, overload of iron results in increased oxidative stress due to the Fenton reaction. We discuss evidence to suggest that sustained exercise and diet restriction may be ways to slow the rate of neurodegeneration, by perhaps promoting neurogenesis or antioxidant-related pathways. It is also our intention to cover NDD in a broad sense, in the context of basic and clinical sciences to cater for both clinician’s and the scientist’s needs, and to highlight current research investigating exercise as a therapeutic or preventive measure.